Fostering Creative Writing through Literature Classes in Primary Education - Θεοχαροπούλου, Γεωργία; Σπαντιδάκης, Ιωάννης (Education Sciences, 2024)
Creative Writing, in a playful manner, aims to stimulate creativity, imagination, authenticity, and self-reflection in written expression. This study examines its cultivation through Literature classes, as they focus on lived experience and subtle nuances of life, enhancing students' emotional awareness and utilization of imagination. The research framework indicates that Creative Writing significantly boosted students' motivation and interest in writing; however, further training of educators is deemed necessary to enhance their competence and confidence in teaching it.